Relasi Fiqh Muamalat dengan Ekonomi Islam - Zainil Ghulam (IQTISHODUNA: Jurnal Ekonomi Islam, 2016)
Association of human society, will lead to personal interests for the sake of self-sufficient. From this will be born the rights and obligations that must be observed as a result of the fulfillment of human life necessities. Every human being bears the rights and obligations of each. Therefore, the association's rights and obligations should be regulated in accordance with the law and order that is clearly not harm each other. For example, every human being must be in need of property or the property of others. To meet these needs, the emerging practice of barter (exchange of goods), then buying and selling directly and are now developing more advanced such as e-commerce. Practices such as these need standards clear law to protect the rights and obligations of each. From here, the Muslim scholars to formulate diligence "rules of the game" are clear and properly conforming the Islamic Sharia, known as Fiqh Muamalat. In Islam, the fundamental philosophy of Islamic Economics is unity of god (Sura 39:38). The concept of monotheism confirms that Allah is the One mighty One, the creator of all beings. Human beings as creatures are derived from the same creation and discount equal rights and obligations as a vicegerent on earth. Thus, in Islamic Economics unknown economic strata, because the principle is the equitable distribution of economic resources for the benefit of human life and the universe. Humans as economic beings (homo economicus) will certainly study the economy as part of his behavior to meet their needs in accordance with the principles prisnip human interaction. Therefore, the pattern of interaction between people (read: Muamalat) in economic practice (Islam), it can be concluded that the real Islamic economic is part of the Fiqh Muamalat.